Cloning, bioinformatics analysis, and expression of the ubiquitin 2 (ubq-2) gene from the dog roundworm Toxocara canis - Zhu, Pengchen; Hu, Xin; Huang, Jiali; Wang, Lidan; Wang, Zhao; Wang, Ruixi; Fan, Xinyi; Wei, Guoshan; He, Qin; Li, Zhaoruiyi; Zhou, Xuan; Wang, Hui; et al. (Frontiers in Veterinary Science, 2025)
Toxocariasis, caused by the dog roundworm Toxocara canis, is a globally distributed zoonotic parasitic disease that poses a significant threat to veterinary and public health. The ubiquitin plus an L40 ribosomal protein (UBQ-2) in parasites plays a crucial role in protein degradation and meiotic divisions, thereby affecting parasite development, survival, and parasite–host interactions. In this study, we identified for the first time a full-length cDNA encoding the UBQ-2 protein from the T. canis-omic dataset, called Tcubq-2. After cloning and sequencing, we conducted sequence analysis and structural modeling of TcUBQ-2 using online bioinformatics tools. The recombinant TcUBQ-2 protein (rTcUBQ-2) was prokaryotically expressed and subjected to Western blot analysis to assess its antigenicity and immunoreactivity. Additionally, we performed immunolocalization of the endogenous protein in adult T. canis and evaluated its serodiagnostic potential using sera from naïve and infected mice and dogs. Our results showed that the complete cDNA sequence of Tcubq-2 was 387 bp in length and encoded a polypeptide of 128 amino acids, lacking both an N-terminal signal sequence and a transmembrane domain. Sequence and phylogenetic analyses showed that TcUBQ-2 shared the closest genetic distance with its homologs in Parascaris univalens and Ascaris suum. Real-time quantitative PCR and Western blotting revealed an expression peak of TcUBQ-2 in the intestine-hatched second-stage (L3) larvae compared to other developmental stages of T. canis. Tissue localization of endogenous TcUBQ-2 revealed its broad distributions in the body wall, muscle, gut epithelium, and microvilli of adult T. canis, with gender-specific expression in the uterus, ovary, and non-embryonated eggs of females. Based on its strong immunogenic properties, a recombinant TcUBQ-2 (rTcUBQ-2)-based ELISA was established and exhibited a sensitivity of 100% and a specificity of 95.8% to detect anti-T. canis mouse sera and a sensitivity of 79.2% and a specificity of 83.3% to detect anti-T. canis dog sera, respectively. This study presents a comprehensive bioinformatics analysis of the dog roundworm TcUBQ-2, and its strong serodiagnostic performance suggests that rTcUBQ-2 has the potential to be developed into an ELISA-based serological test for detecting toxocariasis in dogs and other accidental hosts, including humans.